Convex vacancy creation costs and on-the-job search in a global economy - Christian Holzner; Mario Larch (The World Economy, 2021)
Convex vacancy creation costs shape firms' responses to trade liberalisation. They induce capacity constraints by increasing firms' costs of production. A profit maximising firm will therefore not fully meet the increased foreign demand, but serve only a few export markets. More productive firms will export to more countries and profit more from trade liberalisation. To get an effect of trade liberalisation on wage inequality, we need on-the-job search and convex vacancy creation costs because with linear costs trade liberalisation affects all wages in equal proportion. Furthermore, with convex vacancy creation costs, not all firms export to all foreign markets even if trade is fully liberalised. This implies that wage inequality under free trade is always higher than under autarky.
Keywords: 330; convex vacancy creation costs; heterogeneous firms; international trade; monopolistic competition; on-the-job search